(untitled) (London Journal of Medical and Health Research, 2026)
Over the last few decades, our uderstanding of both the universe and the microscopic world has progressed remarkably. The rise of modern science, bolstered by the evolution of observational instruments, such as the Hubble and James Webb telescopes for cosmic exploration, and next-generation microscopes for the study of living organisms, has led to significant discoveries. Since the invention of the telescope, astronomers have progressively unveiled the structure and dynamics of the universe, establishing the foundations of astrophysics. In parallel, advances in microscopy have enabled the exploration of the infinitely small, revealing the fundamental mechanisms of the human body and laying the groundwork for physiology and molecular biology. Nanotechnology has further refined telescopes and revolutionized medical care, particularly in targeted therapy and regenerative medicine. At first glance, the scales of magnitude inherent to the biological world and those governing the observable universe appear fundamentally disjointed. On one hand, molecular biology explores a microscopic universe: cells, proteins, and subcellular structures, where distances are measured in nanometers or even smaller fractions, expressed in negative powers. On the other, astrophysics deals with objects and structures whose dimensions span light-years, parsecs, and megaparsecs, corresponding to extreme positive orders of magnitude. The systemic complexity of the human organism, much like cosmological structures, simultaneously engages the cognitive, metaphysical, and rational dimensions of the observer. Iconographic data from microscopy and astronomy transcend their purely heuristic function to reveal an intrinsic aesthetic capable of catalyzing intellectual inquiry. These representations facilitate the identification of structural correlations that go beyond simple formal analogy. The emergence of these morphological convergences between radically distinct scales raises a fundamental question: the universality of the laws governing the organization of matter. Drawing on literature data and a comparative analysis of visual patterns, this article proposes to study the convergences between the universe and the human body, the two most complex natural systems identified to date. The central objective is to identify and characterize the multidimensional analogies that unite these two seemingly disparate disciplines. This comparative approach, which remains marginal in conventional scientific literature, moves beyond mere aesthetic observation to address fundamental questions regarding the universality of laws governing complex structures. By exploring intracorporeal architectures as reflections of cosmological dynamics, this work suggests that probing the living organism is, by extension, a means of deciphering the organizational principles that govern the very architecture of the universe.